"Hell is other people": rethinking the Socratic method for quiet law students. Issue 1 (2nd January 2022) - Spencer, Rachel
ABSTRACT: This article is a reflective analysis of my own teaching methodology arising from my experience with teaching quiet law students, and reconciling this experience with a statement in Martin Seligman's Flourish, his best-selling work about positive psychology. Seligman asserts that Jean Paul Sartre's famous line "Hell is other people" in his play No Exit seems "wrongheaded" and "almost meaningless" today. This article will argue that Seligman's comments about Sartre's existentialist angst are the views of an extrovert. This article argues that much of the teaching in legal education today relies on the assumption that law students are extroverts, when the opposite is in fact often the case. It argues that catering only to extroverts is inappropriate. It explores the idea that pushing an aggressive agenda through the Socratic method of teaching diminishes the development of less aggressive legal techniques to resolve problems and ignores the learning needs of students with personalities that tend towards introversion. It argues that the Socratic method of teaching perpetuates a culture that has no place in modern legal practice. It also suggests that progressive approaches to law and dispute resolution require more contemplation, more active listening and less aggressive advocacy, and draws on the work of Susan Cain to demonstrate that recognising the needs and strengths of introverts is important in this process.